DIRECT HF ETCHING-DERIVED Ti3C2TX: A POTENT ADSORBENT FOR BASIC RED 46 DYE - Aksoy, Yunus (My University, 2024)
Dye contamination poses a significant threat to water sources and ecosystems, necessitating the development of efficient treatment methods. Basic Red 46 (BR 46), a highly toxic and persistent azo dye, presents specific challenges in removal from water resources. This study investigates the adsorption efficiency of Ti3C2Tx (Titanium Carbide) MXene, synthesized via direct HF (Hydrofluoric acid) etching, for BR 46 removal. The physicochemical properties of Ti3C2Tx were characterized using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). Additionally, the effects of pH, MXene amount, and initial BR 46 concentration on BR 46 adsorption were also investigated. The results show a maximum BR 46 removal efficiency of 99.98% at pH 2, 4 g/L Ti3C2Tx dose, 50 mg/L BR 46 concentration, and 90 min contact time. This research underscores the potential of Ti3C2Tx MXene as a potent adsorbent for BR 46 dye removal, offering insights for future water treatment applications.
Keywords: Adsorption; Ti3C2Tx; Basic Red 46